2010
DOI: 10.1039/b9pp00122k
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, motivation, and behavior patterns of the general public towards sun protection

Abstract: The general public has long been educated about the harms of ultraviolet (UV) exposure and the benefits of photoprotection. Many organizations have worked in close collaboration to deliver the photoprotection message through a variety of programs. Most address the health-related consequences of UV radiation, although appearance-based strategies have also been initiated. As is common with preventative health measures, these intervention efforts have not resulted in meaningful changes in public behavior despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 67 publications
1
32
0
1
Order By: Relevance
“…As a consequence, the incidence of skin cancers, including melanoma and carcinomas, is in constant increase since the last three decades. The use of sunscreens appears as an appropriate photoprotection strategy because it reduces the UV dose reaching both the dermis and epidermis, and thereby limits the onset of the biological and biochemical processes leading to pathological conditions [3]. A wide variety of photoprotection products is available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the incidence of skin cancers, including melanoma and carcinomas, is in constant increase since the last three decades. The use of sunscreens appears as an appropriate photoprotection strategy because it reduces the UV dose reaching both the dermis and epidermis, and thereby limits the onset of the biological and biochemical processes leading to pathological conditions [3]. A wide variety of photoprotection products is available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…However, many more recent studies in other areas of the world suggested that such success may be incomplete, i.e. , changes in protective behavior had not been fully mirrored the improvement in knowledge [17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on improvements in sun protection and covering up, it has been suggested that children respond best to educational and policy approaches in primary schools. 66 The European Skin Cancer Foundation (http://www.escf-network.eu) and supporting partners have successfully implemented a project aiming at the certification of child day-care centres for their efforts in children's sun-protection activities. The main objectives of the 'SunPass' project are (i) to reduce UV exposure in children, (ii) to raise the awareness of caregivers and parents, and (ii) to reduce skin cancer incidence in the long term.…”
Section: Behavioural and Educational Aspects Of Photoprotectionmentioning
confidence: 99%